Offshore Wind Türbines Worldwide And A Redesigned Offshore Wind Türbine (Aintelia Science Notes, 2022)
Wind has been an energy source for humanity for thousands of years. In the past, wind energy was mostly used in agriculture. With the discovery of electricity, mankind has tried to find new energy sources that can produce electricity. After it was understood that wind turbines, which are mostly used in agriculture in Europe, could be used to generate electricity, wind energy began to be used to generate electricity. An important engineering problem for today and the future is to find and develop alternative energy sources. Wind energy is a renewable energy source with low carbon emissions. In recent years, the number of offshore wind turbines installed on the open sea has been increasing together with the wind turbines installed on land. Located offshore, wind is a clean, renewable energy source with great potential value for the energy industry in the context of a low-carbon society. The fundamentals of offshore wind turbines pose one of the main challenges in offshore wind turbine design. In this article, offshore wind turbines installed in the world and their installed power capacity, types of offshore wind turbines, offshore wind turbine capacity planned to be installed in the future and a static analysis of an offshore wind turbine with a 3D design will be made. A monopile type 3D offshore wind turbine was designed. In this study, the transition piece in monopile type wind turbines has been redesigned considering manufacturability, cost, assembly times and transportation issues, contrary to their classical designs. In this way, the disadvantages of transporting and installing the transition piece as a single piece, which are experienced in classical designs, are eliminated. In the analyzes made on the proposed design, a maximum stress value of 180 Mpa and a maximum displacement of 3.1 mm were observed under a static load of 1687 tons.